Middle-Class Islamist Women’s Activism on Social Media:: A Critical Study of #Womenneedkhilafah - Chasanah, Alifatul Lusiana Uswatun; Zamzami, Mukhammad (Jurnal Komunikasi Islam, 2021)
This article critically discusses the content of tweets expressing Islamist women’s activism on #Womenneedkhilafah, which is mostly followed by Indonesia’s middle-class Muslimah. A qualitative method with the Foucauldian discourse analysis approach is applied in this study. The findings have revealed that the hashtag #womenneedkhilafah is constructed through the knowledge-power relations of Hizbut Tahrir Indonesia’s Islamist ideology grounded in a literal-textual theological argument in which the propagation of Islamism and independent Islamic state or caliphate becomes the main goal. The manifestation of the power-knowledge relation is conducted by limiting women’s role, mobility, and authority over their bodies. HTI limits women’s mobility in "male" public space and considers women's primary role to be the family caregiver, particularly to educate their children and simultaneously to prepare a new and stronger generation of HTI.